Organization of brainstem nuclei - Paxinos, G.; Xu-Feng, H.; Sengul, G.; Watson, Charles (Acadmic Press, Elsevier, 2012)
This chapter presents a classification of the human brainstem structures, including most of neuronal cell groups in the human brainstem. Human homologs of nuclei identified in the brainstem of other mammals are also described as are attempts to extend to the human the overall organizational schemata that have been proposed for the brainstem of other mammalian species. A glaring structural similarity of brainstem across species is reflected by an impressive number of homologies recognized between the brainstem of the human and that of other animals. While it can be hypothesized that there are human homologs to nearly every nucleus identified in the rat brainstem, species differences and even strain differences occur, and this compels us to establish homologies not by extrapolation but by direct observation of human tissue. Functional mechanisms of the human brainstem, on the other hand, remain hidden in connections, chemoarchitecture, and physiology of neuronal groups. These characteristics are emerging from encouraging non-invasive imaging studies and expanding creative application of chemical analysis of the human brain.